2012
DOI: 10.4236/health.2012.47064
|View full text |Cite
|
Sign up to set email alerts
|

Physical functioning: The mediating effect on ADLs and vitality in elderly living in residential care facilities. “Act on ageing”: A pilot study

Abstract: The present study aims at verifying whether participation in a physical activity programme has positive effects on the daily life autonomy and vitality of elderly people living in residential care facilities by the mediation of their physical wellbeing. Fifty-one institutionalised individuals took part in the study. The control group included 11 people (84.26 ± 7.4 years), whereas the experimental group was made up of 40 people (85 ± 6.6 years). The experimental group was involved in a physical activity progra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…52 Other research has shown that participation in a physical activity program has positive effects on participants' sense of vitality due to the mediation of physical functioning. 53 The results of this study showed a significant and direct correlation between flourishing and happiness that is consistent with the results of studies by Keshavarz et al (2005) 18 and Diener et al (2010). 24 One reason for this finding may be that both constructs (flourishing and happiness) are associated with positive emotions.…”
Section: Discussionsupporting
confidence: 93%
“…52 Other research has shown that participation in a physical activity program has positive effects on participants' sense of vitality due to the mediation of physical functioning. 53 The results of this study showed a significant and direct correlation between flourishing and happiness that is consistent with the results of studies by Keshavarz et al (2005) 18 and Diener et al (2010). 24 One reason for this finding may be that both constructs (flourishing and happiness) are associated with positive emotions.…”
Section: Discussionsupporting
confidence: 93%
“…Research has suggested that shoulder abduction declines by five degrees/ decade in men and six degrees/decade in women on average [54]. Upper body flexibility, measured in the present investigation, is essential in executing vital day to day activities such as getting dressed or reaching for objects [55,56] and directly impacts older adults dependence upon staff in long-term healthcare settings.…”
Section: Discussionmentioning
confidence: 81%
“…The perception of physical functioning is probably more strongly correlated to ADL because it is less general and more specific than the self-rated health and pain perception. Taking into account together the three constructs in our study, only the perception of physical functioning has emerged as a potential predictor of ADL (see also [49]).…”
Section: Discussionmentioning
confidence: 93%